1991
DOI: 10.1002/bjs.1800781129
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusion does not promote recurrence and death after mastectomy for breast cancer

Abstract: Several reports suggest that perioperative blood transfusion promotes recurrence and death after cancer surgery. We studied the effect of transfusion in 1599 patients who had mastectomy for carcinoma of the breast. In 228 transfused patients the disease recurred in 110 (48 per cent), compared with 647 (47 per cent) of 1371 non-transfused patients (P = 0.85). The 5-year recurrence-free survival rate was 0.54 in the transfused patients and 0.60 in the non-transfused group (P = 0.44). The transfused patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, contrary results, i.e., no association between perioperative blood transfusion and recurrence have been described. [45][46][47][48][49] In colorectal cancer, it has been reported that perioperative blood transfusion was associated with decreased overall survival but not with recurrence. 50 On the other hand, another investigator has reported that perioperative blood transfusion is associated with decreased time to recurrence as well as overall survival after resection of colorectal cancer liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35] However, contrary results, i.e., no association between perioperative blood transfusion and recurrence have been described. [45][46][47][48][49] In colorectal cancer, it has been reported that perioperative blood transfusion was associated with decreased overall survival but not with recurrence. 50 On the other hand, another investigator has reported that perioperative blood transfusion is associated with decreased time to recurrence as well as overall survival after resection of colorectal cancer liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION A positive association between perioperative blood transfusion and recurrence of colorectal cancer was first reported by Burrows and Tartter in 1982 [l]. Since that time, many clinical studies, both supporting [ 1-81 and disputing [27,28] this association, have appeared in the literature. However, the extent and the mechanism responsible for this association are not clear [8].…”
mentioning
confidence: 94%
“…A few percentages difference in survival may not be important for an individual patient, but it surely gains importance when tens of thousands are in question; administering blood transfusions may be such a prognostic factor. Several years of clinical investigations and many studies yielding opposite results (with the majority of them, including the one with the largest sample size of 1,599 [5], stating that blood transfusions do not deteriorate survival in breast cancer patients), clearly points to the conclusion that blood transfusions may either be insignificant for breast cancer patients or their affect on survival is small at best. Quite often, however, previous studies on that subject were not particularly large, which certainly does not help to resolve clinical dilemma in regards to weak prognostic factors.…”
Section: Discussionmentioning
confidence: 91%
“…This issue, however, is still unresolved. Although some studies claimed an unfavorable effect of blood transfusions on survival of cancer patients [1][2][3], others did not [4][5][6][7][8]. It is unlikely that large, properly designed, randomized trials will clarify this matter.…”
Section: Introductionmentioning
confidence: 99%